Significant enhancement in the performance of porphyrin for dye-sensitized solar cells: Aggregation control using chenodeoxycholic acid - Jungsuttiwong S. (2017)
© The Royal Society of Chemistry and the Centre National de la Recherche Scientifique 2017. In this work, a series of porphyrin-based sensitizers, coded as ZnTEP, ZnTTEP, and ZnTTTD in which different kinds of thienyl groups are used as the π-linker, have been designed and successfully synthesized. Their synthesis, photophysical and electrochemical properties, and theoretical DFT calculations, as well as their applications in dye-sensitized solar cells (DSSCs) are reported. The results showed that the power conversion efficiency (η) increases in the order of 1.14, 2.15 and 3.51% for ZnTEP, ZnTTEP and ZnTTTD, respectively. A significant improvement in the η value was achieved with ZnTTTD-based solar cells, which was approximately three times the magnitude when compared to the lowest ZnTEP-based solar cells. Moreover, the effects of chenodeoxycholic acid (CDCA) in a dye solution as a co-adsorbent on the photovoltaic performance of DSSCs were investigated. It was found that the coadsorption of CDCA can hinder the formation of dye aggregates and the improve electron injection yield and thus J sc . The η value for ZnTTTD with the CDCA co-sensitizer dramatically increases up to 6.51%. This understanding of π-linker and co-sensitizer effects on the performance of porphyrins will serve as a guideline for the design of future dye sensitizers for DSSCs.